PROSES DECISION MAKING DENGAN MELIBATKAN STAKEHOLDERS SEKOLAH - Agus Fahmi (Jurnal Paedagogy, 2014)
This study aims to describe all phenomena and events that occur in relation to the principal's decision making in implementing school work programs, which include: (1) The decision-making process, (2) the involvement of teachers, school personnel, and the community, and (3) Implementation school work program. The approach used in this research is qualitative, with a multi-site study design. The research data is in the form of descriptive data obtained through interviews, documentation and observation. Data analysis used modified analytical induction techniques (modified analysis) in the form of on-site data analysis and cross-site data analysis. There are four types of data validity checking, namely credibility, transferability, dependability, and confirmability. The results of the study are summarized as follows. First, the decision-making process consists of, (1) problem identification, (2) determination of problem-solving criteria, (3) identification of alternatives, (4) assessing alternatives from a series of alternatives, (5) choosing the best alternative, and then, (6) implementation of alternatives Second, the involvement of school stakeholders, namely the involvement of teachers, school personnel, and the community as follows: (1) participation of teachers in schools in implementing learning programs, (2) involvement of school staff in administrative processes and technical matters to support the achievement of school goals and (3) involving the committee and parents of students in making decisions. Third, the results of the decisions are in the form of implementing school work programs which include the implementation of curriculum, student affairs, sarpras, finance, and public relations, including: (1) implementation of effective learning programs, (2) ) improving the quality of schools through discipline, (3) developing students' interests and talents through sports and arts activities, (4) solving problems faced by students.